The battle of Atlah and its importance in the history of middle Sirdarya basin - Burkhanadin, A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
In this article, will be discussed the historical battle that took place in 751 July in Atlah near the current city of Taraz and its consequences for the future of the Middle Sirderian basin. In this war for the first time Turks and Arabs have fought shoulder to shoulder and won the war against Chinese. The results of the war have not only left a mark on the region but also on a worldwide scale. Because with the knowledge of Chinese paper makers taken captive after this war, Muslims were able to open the first paper mills in Samarkand. Another thing worth noting is that after a several centuries production of paper has passed to Europe through Andalusia. So the war of Atlah can be called important in terms of the cultural history of the world. The issue is as important as the current Kazakh nation, and as for all Turkish-born peoples. Because this single war decided their future. Most historians have touched details of this war briefly, however, the general course of the war and its consequences have been untouched. In this article, the author will elaborate on the subject using classical Arabic and other valuable sources on this field. It will also deal with the political incidents and relations between the Abbasid caliphs and the Turkish slaves that took place in the region in the following years from the war. Key words: Atlah, muslims, Sirdarya, Abbasids, war, Turks, Arabs, slave, culture, Chinese, Karluks, chaliph.